Practical recommendations for the prevention of surgical complications related to the procedure of the interalveolar osteotomy - S. G. Ananyan; A. V. Zakaryan; M. V. Gunko; Sh. R. Gvetadze (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The article examines possible medical errors during the interalveolar osteotomy that may negatively affect the effectiveness of the treatment. It also analyses the basic techniques that provide adequate vitality of the tissues in the place of surgery. It also demonstrates the necessity of the reconstruction of the full thickness of the gum in order to achieve long-term esthetic results in the area of dental implantation.